The Effect of a Regular Auditory Context on Perceived Interval Duration - Zeni, Silvia; Holmes, Nicholas P. (Frontiers in Psychology, 2018)
In the auditory domain, the perceived duration of time intervals is influenced by background sounds - the auditory context in which the intervals are embedded - even when the background may be ignored. Previous research has shown that a regular context made of evenly spaced sounds improves participants' discrimination of intervals close in duration to the context intervals. These results have been explained in terms of attention and anticipation. The present study reconsiders the effect of context regularity, focusing on the relationships among the intervals in the context and the interval to be estimated. The influence of a regular compared to a non-regular auditory context on interval discrimination was examined with a two-interval forced choice task, which required participants to discriminate between the durations of two time intervals. Duration perception was more accurate and precise when the intervals to be discriminated were preceded by a regular compared to a non-regular context. This effect of the regular context, however, was not selective for the duration of the first interval to be estimated, contrary to suggestions based on previous evidence.